Serum Selenium Levels in Glaucoma: A Pilot Study - Lucio, Marianna; Fick, Alexander; Michalke, Bernhard; Lämmer, Robert; Hosari, Sami; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Trace elements are assumed to be involved in glaucoma pathogenesis via changes in oxidative stress. Especially serum selenium (Se) has been linked to this neurodegenerative disease. Serum Se levels differ between countries due to nutrition and ethnicity. It was the aim of the present study to investigate serum Se levels in primary open-angle glaucoma (POAG) patients and controls in Germany and to consider potential age and gender effects. Material and Methods The Se concentration of 39 serum samples (22 patients with POAG, 17 controls) were analyzed by inductively coupled plasma-sector field mass spectrometry (ICP-sf-MS) in high resolution mode. Covariance and percentile regression were analyzed. Age and gender were defined as confounding factors and their different trends were investigated. Moreover, age was examined across different quantiles of Se levels. Results Total serum least-squares means (LS-means) Se levels were 132.02 μg/L (controls) and 134.86 μg/L (POAG). Total serum Se levels did not differ between the study groups (p > 0.05). Significant age and gender effects of serum Se were observed. Quantile analysis showed that the 1st serum Se quantile decreased with increasing age in POAG patients in contrast to controls. The odds ratios of the 1st serum Se were 1.3 (with 2nd quantile) and 1.3 (with 3rd quantile), respectively. Conclusion The serum Se level of the German cohort was almost half of those of the published US cohort (glaucoma 209.11 ng/mL; control 194.45 ng/mL). Age and gender effects were observed; the serum Se level increased with age in women (controls and POAG), however, Se levels decreased with age in men (controls and POAG).
CRIS-Team Scopus Importer:2021-03-05
Keywords: age; gender; glaucoma; ICP-sf-MS; selenium; trace element